Republic of Congo: Agricultural R&D Indicators Factsheet - Magne Domgho, Lea Vicky; Bani, Grégoire; Flaherty, Kathleen (International Food Policy Research Institute, 2017)
This country factsheet presents key agricultural R&D indicators in a highly accessible visual display. The publication also feature a more in-depth analysis of some of the key challenges that the country’s agricultural R&D system is facing, and the policy options to address these challenges.